1997
DOI: 10.1046/j.1570-7458.1997.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition preference of western flower thrips for cucumber leaves from different positions along the plant stem

Abstract: While the distribution of herbivorous insects over leaves along the stem often shows a peak at some distance from the apex this does not necessarily reflect an innate preference as alternative explanations can be provided such as impact of predators and inter‐ or intraspecific competitors. It is of interest to determine which factors shape the distribution of insects over the leaves of a plant. Do leaves from different positions differ in suitability for insects and is that reflected in the insect's preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Before the start of the experiment, adult females 5Ð 6 d old (F. occidentalis females start laying eggs, on average, at 3 d postemergence at 20 Ð25ЊC; Marullo and Tremblay 1993) from the same cohort were collected with an aspirator and kept in petri dishes for 24 h to acclimatize them with the experimental arena. After 24 h, 20 females were released at the center of each petri dish and allowed to oviposit on the leaf discs for 24 h. The petri dish was covered with 105-m mesh, and the edges were sealed with parafÞn Þlm (de Kogel et al 1997). After 24 h, F. occidentalis adults were removed, and each leaf disc was transferred onto moistened Þlter paper in separate petri dishes and covered with paraÞlm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the start of the experiment, adult females 5Ð 6 d old (F. occidentalis females start laying eggs, on average, at 3 d postemergence at 20 Ð25ЊC; Marullo and Tremblay 1993) from the same cohort were collected with an aspirator and kept in petri dishes for 24 h to acclimatize them with the experimental arena. After 24 h, 20 females were released at the center of each petri dish and allowed to oviposit on the leaf discs for 24 h. The petri dish was covered with 105-m mesh, and the edges were sealed with parafÞn Þlm (de Kogel et al 1997). After 24 h, F. occidentalis adults were removed, and each leaf disc was transferred onto moistened Þlter paper in separate petri dishes and covered with paraÞlm.…”
Section: Methodsmentioning
confidence: 99%
“…Beakers were placed into a microwave oven and heated for 3 min (700 W) (de Kogel et al 1997). Leaf discs were soaked in methyl red and examined under a stereomicroscope (40ϫ magniÞcation) for unhatched eggs.…”
Section: Methodsmentioning
confidence: 99%
“…Randomly collected female thrips from a single population, were put on the leaf discs (10 females/disc, 4 leaf discs/accession). After 2 days of adaptation, thrips were transferred to fresh leaf discs (10 females/disc, 4 leaf discs/accession) where they were allowed to oviposit for 24 h. After 4 days the Kogel et al (1997) showed that numbers of larvae and numbers of eggs are strongly correlated, therefore, reproduction was expressed as number of larvae/female/day. In each separate experiment, reproduction of thrips from two or three populations was determined.…”
Section: Reproduction Test With Randomly Collected Femalesmentioning
confidence: 99%
“…The reproduction of isofemale lines differed on bean (Phaseolus vulgaris L.) and cucumber (De Kogel 2003). Moreover, F. occidentalis preferred younger over older cucumber leaves for oviposition, and leaf age seems to influence other behaviours as well: The thrips spent more time walking on older leaves (De Kogel et al 1997).…”
Section: Discussionmentioning
confidence: 99%